Local Wisdom as an Instrument of Disaster Risk Management: Reconstructing Local Government Roles in the Governance of Local Knowledge - Lalu Ahmad Murdhani (International Journal of Scientific Research, 2025)
This study examines local wisdom as an instrument of disaster risk management and reconstructs the role of local government in the governance of local knowledge. The study is grounded in the argument that community-based knowledge, indigenous practices, oral histories, ecological observations, customary norms, and social memory are often crucial in helping communities understand hazards, interpret risk, and organize collective preparedness. However, such knowledge frequently remains outside formal disaster governance systems, which tend to prioritize scientific data, technological warning systems, administrative procedures, and sectoral coordination. Using a qualitative case study approach, this research analyzes how local wisdom is recognized, documented, validated, and integrated into formal disaster risk reduction mechanisms. Data were collected through in-depth interviews, field observations, and document analysis involving local government actors, disaster management agencies, traditional leaders, community representatives, and disaster volunteers. The findings show that local wisdom functions as an early recognition system, a behavioral guide, and a social coordination mechanism in disaster risk management. Nevertheless, its institutional integration remains limited due to weak documentation, fragmented coordination, and the absence of clear policy mechanisms for local knowledge governance. This study contributes to disaster governance literature by proposing a reconstructed role for local government as a knowledge broker, facilitator, regulator, and institutional integrator. The novelty of this study lies in bridging local, indigenous, and traditional knowledge with formal governmental systems so that disaster risk reduction becomes more participatory, culturally grounded, and institutionally sustainable.